Indonesia Stock Market Reaction Before and After The Announcemnet of First COVID-19 Case - Ades Kurnia; Restu Agusti; Julita Julita (Asosiasi Fakultas Ekonomi dan Bisnis Indonesia, 2022)
This study aims to analyze the effect of COVID-19, which announced on March 2nd, 2020 in Indonesia on abnormal return, volatility, trading volume and market capitalization of companies 10 days before and after the announcement. This type of research is an event study. The populations are 70 firms listed on the JII70 and 12 firms on SRI-Kehati on the Indonesian Stock Exchange and take all companies in the issuer under study as samples. Hypothesis testing will use the paired sample t-test for abnormal return and volatility variables then wilcoxon signed-rank test for trading volume and market capitalization variables. The results of the study show that there is no difference in abnormal return but there is a difference in volatility, trading volume and market capitalization before and after the announcement of COVID-19 in Indonesia.